Qualitative multi-criteria approaches to assessing indicators of sustainable forest resource management - Mendoza, G.A.; Prabhu, Ravi (2003)
Criteria and indicators (C&I) have become primary tools in implementing the principle of sustainable resource management. To carry out this principle, it is necessary to develop methodologies that can holistically and systematically generate relevant indicators for a particular forest or resource management unit. This paper describes some methodologies that can be used as tools to carry out structured analysis of C&I. Multi-criteria analysis (MCA) is used as a decision-making tool to analyze and evaluate multiple C&I under a participatory group decision-making environment. Use of the method enables the generation of C&I, estimation of their relative importance, estimation of the performance of each indicator relative to its desired condition, and assessment of the indicators' combined effect or impact. In addition to generating C&I and estimating their relative importance and performance, the paper also presents a soft methodology, called cognitive mapping, which can be used to assess the cross indicator interaction, linkages, and connectivities of the indicators. The method attempts to evaluate the overall cumulative impacts of all indicators, individually and collectively, as they impact sustainability directly and indirectly through their interactions with other indicators.